CONTENT ANALYSIS OF SOCIAL CRITICAL IN ANTITANK-PROJECT INSTAGRAM ACCOUNT - Wipti Aga Pramasepta; Christina Rochayanti; Kartika Ayu Ardhanariswari (The Indonesian Journal of Communication Studies, 2020)
Criticism is one element that can keep the existing system in its tracks and not get out of the way the system should be. Anti-tank has initially been one of the artists and activists who expressed their criticism using posters in Yogyakarta. This study aims to determine the content of criticism in the Antitank Project and the tendency of criticism. The method is content analysis. The theory used is the spiral silence theory and Habermas' critical theory. The study population amounted to 192 images in the period of January 2016 - December 2018. The study sample was taken 46 pictures to be examined because of the repetition of several photographs. The research results show that there is a tendency in Antitank criticism, namely in the political field, in which there is an important element of power and has high publicity. The object of criticism of Anti-tank's dominant work is the state government, which holds the country's highest authority. Communication of indirect criticism works or symbols becomes dominant in Antitank social criticism works. The use of symbols is more interesting and wise, to reduce conflict with the object of criticism. Antitank uploads through Instagram to get broad support and increase the approach to his work to cause movement to a broad audience by the theory adopted, namely the spiral of silence theory.